2009
DOI: 10.1159/000229306
|View full text |Cite
|
Sign up to set email alerts
|

The Activities of Paraoxonase, Xanthine Oxidase, Adenosine Deaminase and the Level of Nitrite in Pseudoexfoliation Syndrome

Abstract: Aim: Our purpose was to investigate the possible roles of nitrite levels and the activity of paraoxonase (PON), xanthine oxidase (XO) and adenosine deaminase (ADA) in the pathogenesis of pseudoexfoliation (PEX) syndrome. Methods: Serum samples were taken from 43 patients with PEX and 41 control subjects. The serum PON, XO and ADA activities and nitrite levels were assayed by spectrophotometric methods. Results: The PON, ADA and XO activities and nitrite levels (means ± standard deviation) were 81.72 ± 42.56 U/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 67 publications
(39 reference statements)
0
13
1
Order By: Relevance
“…Sex was shown to affect XO, although it is still controversial [24][25][26][27]. One of the possible reasons for the contradictory result can be the gender distribution among test groups which was not stated by Yagci et al [4]. In our study, distribution of sex in the PEX and normal groups was the same (Table 2).…”
Section: Discussioncontrasting
confidence: 41%
See 4 more Smart Citations
“…Sex was shown to affect XO, although it is still controversial [24][25][26][27]. One of the possible reasons for the contradictory result can be the gender distribution among test groups which was not stated by Yagci et al [4]. In our study, distribution of sex in the PEX and normal groups was the same (Table 2).…”
Section: Discussioncontrasting
confidence: 41%
“…Because PEX is SD standard deviation, n/a not applicable, BUN blood urea nitrogen, AST aspartate aminotransferase, ALT alanine aminotransferase, WBC white blood cell, HGB hemoglobin, HCT hemotocrit, PLT platelet, APTT active parsiel prothrombin time, PT prothrombin time, INR international normalized ratio known as a systemic disease, we decided to determine serum XO levels of PEX. In this study, we found that serum levels of XO in subjects with PEX were not different than a normal group (Table 3), although higher serum XO in PEX was reported by Yagci et al [4]. We used a colorimetric method for quantification of serum and aqueous XO, while Yagci used a spectrophotometric method [23].…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations